Dynamics layer of the sliding contact collector elements; 2015 IEEE 35th International Conference on Electronics and Nanotechnology (ELNANO 2015) - Romanishina S. A.; Katyuk D. Yu. Diana Yurjevna; Deeva V. S. Vera Stepanovna; Slobodyan S. M. Stepan Mikhaylovich (2015, 2015)
Title screen